The roles of knowledge intermediaries in sustainability transitions and digitalization: Academia driven fostering of socio technical transitions? - Philipp Bäumle; Daniel Hirschmann; Daniel Feser (Volkswirtschaftliches Institut für Mittelstand und Handwerk an der Universität Göttingen (ifh), 2022)
The concept of intermediation is central to current approaches to innovation policy. While the extant literature distinguishes between academia driven knowledge intermediaries supporting the commercialization of academic knowledge and public intermediaries focusing on the support of socio technical transition processes, little is known about the roles and activities of knowledge intermediaries in sustainability transitions and digitalization, even though the systemic coaction of different intermediaries is essential for policy making. This understudied issue is explored using an explorative-qualitative approach and empirical evidence from interviews of participants in regional knowledge intermediation initiatives. We find that knowledge intermediaries proactively contribute to the two socio technical transitions in question by performing three roles: (i) information dissemination via events, (ii) knowledge exchange via network building, and (iii) implementation support via consulting. Furthermore, we identify additional roles concerning the identification and monitoring of new projects emerging from the interplay between sustainability and digitalization. Working at the intersection of both transitions and cognizant of the effects of digitalization on sustainability, knowledge intermediaries are key actors in fostering digitalization processes that preclude rebound effects on sustainability or contribute to sustainability transitions. This paper contributes to current scholarly discussions by closing the conceptual gap between knowledge and transition intermediaries and emphasizing the interdependencies between digitalization and sustainability.
Keywords: I29; O32; O39; Q29; 330; knowledge intermediaries; transition intermediaries; sustainability transition; digitalization; higher education institutions; qualitative case studies